2019
DOI: 10.1108/ijcst-03-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Suitable bustline position in designing a well-fitting and attractive garment

Abstract: Purpose The purpose of this paper is to investigate a suitable position for the bustline of the upper garment and its effect on appearance for various body types. It also provides an appropriate balance between the bustline and the waistline. Design/methodology/approach The authors manufactured five upper garments using a patternmaking method that allows for the distance between the side neck point and the bust point (BL) to be altered. The appearance of the garments on four dress forms with different values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Six items shall be assessed; wrinkles, fit, attractiveness, beauty, and slimming. This study helps manufacturers create beautiful, high-quality clothing [15]. One of the studies showed that the process of draping around the neckline may differ from one design to another, depending on the desired pattern block and the method of making the pattern block, but these methods could be used in the lower part of the clothes such as skirts, dresses, and pants.…”
Section: Introductionmentioning
confidence: 99%
“…Six items shall be assessed; wrinkles, fit, attractiveness, beauty, and slimming. This study helps manufacturers create beautiful, high-quality clothing [15]. One of the studies showed that the process of draping around the neckline may differ from one design to another, depending on the desired pattern block and the method of making the pattern block, but these methods could be used in the lower part of the clothes such as skirts, dresses, and pants.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of denim fabrics, the association between physical properties of fabrics and users' subjective hand feel is explained (Kawamura et al , 2016). Kim (Kim et al , 2020) investigated a suitable position for the bustline of the upper garment. It can be seen that in the field of clothing design, most research on user perception focuses on a certain design element, but the study of a single design element can hardly provide a guide for the optimization of the overall design of a clothing product.…”
Section: Introductionmentioning
confidence: 99%
“…However, that research examined a basic pattern for clothing: the appearance of the garment was not considered. Kim et al (2019b) investigated suitable bust line positions in the upper garments. However, they did not investigate the effect of ease allowance.…”
Section: Introductionmentioning
confidence: 99%